Diversity and Novelty of Venom Peptides in Vermivorous Cone Snails, Subgenus Rhizoconus (Gastropoda: Mollusca) - Christine Marie C. Florece; Quentin Kaas; Neda Barghi; Arturo O. Lluisma (Marine Drugs)
A large majority of cone snails (a species in the genus Conus) are vermivorous (worm-hunting), but the diversity and bioactivity of their venom peptides remain largely unexplored. In this study, we report the first venom gland transcriptomes from two species in the Rhizoconus clade, Conus capitaneus and Conus mustelinus, and a new Conus miles transcriptome from a specimen collected in the Philippines. From the set of assembled sequences, a total of 225 C. capitaneus, 121 C. miles, and 168 C. mustelinus putative peptide toxin transcripts were identified, which were assigned to 27 canonical gene superfamilies in C. capitaneus and 24 in C. miles and in C. mustelinus. Most of these venom peptides are novel, and some exhibit new cysteine patterns. Clustering also revealed 12 putative novel gene superfamilies, highlighting the diversity of uncharacterized venom peptides in this group. The O1-, M-, O2-, and con-ikot-ikot superfamilies were the most abundant, while gene superfamilies such as D and G2 were highly expressed. Several hormone-like conopeptides were also identified in this study, revealing the vast diversity of conopeptides from the Rhizoconus species.